The Past, Present, and Future of a Human T-Cell Leukemia Virus Type 1 Vaccine - Tu, Joshua J.; Maksimova, Victoria; Ratner, Lee; Panfil, Amanda R. (Frontiers in Microbiology, 2022)
Human T-cell leukemia virus type 1 (HTLV-1) is an oncogenic human retrovirus which causes a lifelong infection. An estimated 5–10 million persons are infected with HTLV-1 worldwide – a number which is likely higher due to lack of reliable epidemiological data. Most infected individuals remain asymptomatic; however, a portion of HTLV-1-positive individuals will develop an aggressive CD4+ T-cell malignancy called adult T-cell leukemia/lymphoma (ATL), or a progressive neurodegenerative disease known as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Few treatment options exist for HAM/TSP outside of palliative care and ATL carries an especially poor prognosis given the heterogeneity of the disease and lack of effective long-term treatments. In addition, the risk of HTLV-1 disease development increases substantially if the virus is acquired early in life. Currently, there is no realistic cure for HTLV-1 infection nor any reliable measure to prevent HTLV-1-mediated disease development. The severity of HTLV-1-associated diseases (ATL, HAM/TSP) and limited treatment options highlights the need for development of a preventative vaccine or new therapeutic interventions. This review will highlight past HTLV-1 vaccine development efforts, the current molecular tools and animal models which might be useful in vaccine development, and the future possibilities of an effective HTLV-1 vaccine.